Performance of a Three-Dimensional Electrochemical Reactor (3DER) on Bisphenol A Degradation - Ren, Xu; Song, Kai; Zhang, Qiaoyun; Xu, Linghan; Yu, Zhuyi; Tang, Peixin; Pan, Zhicheng (Frontiers in Chemistry, 2022)
This study constructed a three-dimensional electrochemical reactor (3DER) using meshed stainless steel sheet and titanic magnetite particles (TMP) to investigate the Bisphenol A (BPA) degradation through the synergistic action of electrical current and TMP. We examined some TMP characteristics, such as particle size, specific surface areas, X-ray diffraction, surface imaging, elemental constituents, and electrical resistivity. It was found that TMP was a micron-level material with excellent electrical conductivity, and it could be regarded as a magnetite-based material comprising Fe(II) and Fe(III). The single-factor experiment determined the optimal conditions for BPA removal in 3DER, specifically by introducing 200 mL of BPA simulated wastewater (10 mg∙L-1) into 3DER. At the initial pH of 9.00, current and electrodes gap of 300 mA and 15 mm, respectively, and adding 1 mL of 0.5 M potassium peroxymonosulfate and 1 g TMP, >98% of BPA was removed after 55 min of electrochemical reaction. Additionally, liquid chromatography-mass spectrometry identified the intermediates formed during the BPA treatment, showing two possible pathways for BPA degradation. The final degradation intermediates were chain organics with simple molecular structures. This research provided an understanding of the potential application of 3DER for BPA removal in water.